The Effect of a Bonus Program for Preventive Health Behavior on Health Expenditures - Boris Augurzky; Arndt R. Reichert; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This paper contributes to the analysis of policy measures that attempt to reduce health care expenditures of insurers. We examine the impact of a cash bonus program for preventive health behavior of a German health insurer on prevention eff ort and health care expenditures using a unique administrative dataset that covers all insurants of the health insurer between 2003 and 2008. We fi nd that the program has been successful in both increasing individual prevention eff ort and achieving net savings every year since its implementation in 2004. However, while the estimated eff ect on health care expenditures is statistically signifi cant in the fi rst year, the effects for the second, third, and fourth years turn insignifi cant. In the fi fth year, results for net savings are sensitive in terms of statistical signifi cance when accounting for dynamic selection into the treatment. – – Diese Studie untersucht die Wirkungen eines Bonusprogramms für gesundheitsbewusstes Verhalten auf das individuelle Präventionsverhalten und die Gesundheitsausgaben von teilnehmenden Versicherten einer deutschen gesetzlichen Krankenversicherung. Die Analyse stützt sich auf einen einzigartigen, administrativen Datensatz, der zwischen 2003 und 2008 die Gesundheitsausgaben aller Versicherten dieser Krankenkasse enthält. Die Ergebnisse zeigen, dass das Bonusprogramm seit der Einführung in 2004 jedes Jahr aufs Neue die individuellen Präventionsanstrengungen der Teilnehmer erhöht und die Gesundheitsausgaben reduziert hat. Während der Effekt auf die Gesundheitsausgaben im ersten Jahr statistisch signifikant ist, werden die Effekte für das zweite, dritte und vierte Jahr jedoch insignifikant. Die Ergebnisse hinsichtlich der Nettoprogrammeinsparungen sind im fünften Jahr sensitiv gegenüber der Berücksichtigung von dynamischen Selektionseffekten.
Keywords: I10; I12; I18; 330; financial incentives; health care expenditures; dynamic treatment effect; health prevention; inverse probability weighting; bonus program; Gesundheitsvorsorge; Gesundheitskosten; Leistungsanreiz; Gesetzliche Krankenversicherung; Deutschland